Pengaruh Penggunaan Tinta Buatan pada Pancing Tuna Terhadap Jumlah Hasil Tangkapan - Tri Setianto; Muhammad Maskur; Tamrin Tamrin; Khairudin Isman; Arham Rumpa; Nurwahidin Nurwahidin (Jurnal Airaha, 2020)
Tuna is one of the mainstay commodities of South Sulawesi Province. The use of ink attractants to attract or lure Tuna, especially those made from non-food grade ingredients (can not be consumed) is increasingly widespread, but has the potential to pollute the environment. This study aims to compare the number of catches (volume) between tuna fishing rods with attractants made from screen printing ink (non food grade) with ink atractant made from food coloring. The experimental method used in this study was to collect data on the number of catches () of the two types of treatment on the tuna fishing rod at the fishing location. Data on the number of catches collected was then analyzed using Variance Analysis (ANOVA) patterned randomized block design (RBD). The results showed that the number of catches of tuna fishing with non-food-grade ink attractants is more than tuna fishi`ng lines with food-grade ink attractants. The analysis showed that the calculated F value for the treatment was 43.587 and the group was 8.956, greater than the F table value at the real level of 95% which meant that there were differences between the two forms of treatment and the group. Non-food-grade ink has an adequate level of viscosity because it does not dissolve quickly in seawater so that it is thought to attract or attract more attention or vision of Tuna fish to more aggressively grab the bait compared to food-grade ink. The focus of future research is to improve the performance of fishing line with food-grade ink to be more environmentally friendly.